The Analysis of E-service Quality, Customer Trust, Perceived Value, and Behavioral Intention on Online Transportation in Surabaya - Putrianti, Anindya Selviana; Semuel, Hatane (Petra International Journal of Business Studies, 2018)
The current number of motor vehicles in Indonesia increased very rapidly and impacted the traffic jam. Therefore, it was expected that with the increasing use of public transportation can reduce congestionproblems. Competition in the transportation industry is gotten competitive, so there is an innovation withmobile applications. But to make consumers want to use online transportation applications, companies mustunderstand about consumer behavior. Measurement of behavioral intention is the best way to predictconsumer buying behavior in the future. In this study, we wanted to know the factors that affect thebehavioral intention of online transportation consumers in Surabaya. This research used causal quantitativeresearch method. Based on the results of research conducted on 240 respondents found that e-service quality,trust and perceived value correlated significantly and positively to behavior intention. E-service quality is themost influential factor in building behavior intention compared to the other two factors.